The Differences in Enhancing Students' Mathematical Communication Skills and Learning Independence Between CTL and STAD Models on Polynomial Material - Siregar, Rudi; Mukhtar, Mukhtar; Nasution, Hamidah (Jurnal Perspektif, 2025)
This study aims to determine the effect of Initial Mathematical Ability (KAM) on students' mathematical communication skills and student learning independence; to determine whether there is an interaction between the learning model and KAM on improving students' mathematical communication skills and student learning independence. This research method is a quasi-experimental one. The population of this study was all students of class XI MAN 2 Deli Serdang in the 2024/2025 Academic Year totaling 432 consisting of four medical majors, three Science and Technology, three Social Sciences and two Islamic majors, while the research sample was class XI Medical 3 (Experiment 1) and XI Science and Technology 3 (Experiment 2). The results of the study showed that there was an effect of KAM on students' mathematical communication skills and learning independence; there was a difference in improving mathematical communication skills and learning independence; and there was an interaction between initial mathematical abilities and mathematical communication skills and learning independence